Structural Reforms in Agrarian Sector of Economy, Stages and Results: Problems of Modernization and Import Substitution - A. A. Shutkov (Модернизация, инновация, развитие)
Purpose: the aim of the article is to study the reasons for the decline in agricultural production, withdrawal from the market of tens of millions of hectares of cultivated areas, reduction of livestock and poultry. Justiﬁcation of the importance of the use of domestic and foreign experience of state regulation of economic relations, the ﬁnancial support for the development of agricultural production. This article analyzes the structural changes in the agricultural sector of the Russian economy in the post-reform period, with an emphasis on solving problems of modernization of agricultural production. The stages of structural reforms, their characteristics, which are based on the methodological approaches related to the adoption and implementation of normative acts of the federal authorities with an estimate of the dynamics of agricultural production and the state of the economy producers has been reviewed. Methods: the methodological basis of this article are the economic and statistical methods of analysis, regulatory documents in the ﬁeld of food security, public analytical materials in the ﬁeld of the problems of modernization and import substitution. Results: the results of the work became – development of proposals addressing the problems of increasing efficiency of structural reforms. The necessity of the following was proven: the transition of the agricultural sector in the resource-innovative development model based on the integration of science and production; adjustment of the State program of agricultural development and regulation of agricultural products, raw materials and food for 2013–2020 in terms of economic relations; improvement agro-industrial production management mechanism. Conclusions and Relevance: structural reforms in the agricultural sector as a result of errors did not contribute to the sustainable growth of its efficiency, which lead to a sharp decline in production, the country has lost food independence. It is necessary to develop a qualitatively new development program of agricultural production in view of its ongoing modernization, the transition to resource-innovative model of operation.